Eksplorasi Etnomatematika Masyarakat Pesisir Selatan Kecamatan Puger Kabupaten Jember: Exploration of Ethnomathematics in the Coastal Community of Puger District, Jember Regency - Indah Wahyuni (Fenomena, 2016)
The idea of ethnomathematics can enrich mathematical knowledge. If the development of ethnomathematics has been studied, it means that mathematics is taught by incorporating local culture. According to Bishop (1994b), mathematics is a form of culture that integrates into all aspects of society. Essentially, mathematics is a symbolic technology that grows from culturally rooted skills or environmental activities. Thus, an individual's mathematics is influenced by their cultural background, as what they do is based on what they see and feel. Culture affects individual behavior and plays a significant role in developing understanding, including mathematical learning (Bishop, 1991). Mathematics education is inherently intertwined with societal life, contrary to the conventional view that mathematics is a culture-free and value-free science. Ethnomathematics experts argue that the development of mathematics cannot be separated from the culture and values present in society. Gagasan etnomatematika dapat memperkaya pengetahuan matematika. Jika perkembangan etnomatematika telah dikaji, berarti matematika diajarkan dengan memanfaatkan budaya lokal. Menurut Bishop (1994b), matematika merupakan bentuk budaya yang terintegrasi dalam semua aspek masyarakat. Pada hakikatnya, matematika adalah teknologi simbolis yang tumbuh dari keterampilan atau aktivitas lingkungan yang bersifat budaya. Dengan demikian, matematika seseorang dipengaruhi oleh latar belakang budayanya, karena apa yang mereka lakukan berdasarkan apa yang mereka lihat dan rasakan. Budaya memengaruhi perilaku individu dan berperan besar dalam pengembangan pemahaman, termasuk pembelajaran matematika (Bishop, 1991). Pendidikan matematika sebenarnya telah menyatu dengan kehidupan masyarakat, bertentangan dengan konsep konvensional yang memandang matematika sebagai ilmu yang bebas budaya dan nilai. Para ahli etnomatematika berpendapat bahwa perkembangan matematika tidak terlepas dari budaya dan nilai yang ada dalam masyarakat.